The Influence of Product Quality, Green Advertising and Environment Awareness on the Purchase Decision of Aqua Brand Packaged Drinking Water Products - Hidayati, Dewiana Nur; Harsoyo, Titik Desi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the influence of product quality, green advertising and environment awareness on purchasing decisions for Aqua brand bottled drinking water. The sample consisted of 100 consumer respondents who had purchased Aqua products. Data were collected through a survey using a questionnaire. The research indicate that: Product quality has a positive and significan influence on consumer purchasing decision for Aqua products, Green Advertising and Environmental Awareness does not have a significan influence on consumer purchasing decisions for Aqua products.